Pengaruh Job Crafting Terhadap Work Engagement Pada Karyawan Bagian IT PT X - Mochamad Rokib Vadya Mulyadi; Rizka Hadian Permana (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The effect of job crafting on work engagement in the IT sector is something that has not been studied much, so this research was conducted to complete this deficiency. This research was conducted on employees of the IT department, especially on a programmer who makes a website or software. This research method is used causal method within 32 subjects employees of the IT department of PT X. This study uses a psychological scale with a job crafting scale from Tims, Bakker, Derks and a work engagement scale from Schaufeli & Bakker. The results of this study show that